A Postcolonial Exploration of Finnish Engagement in North-South Higher Education Capacity Development Partnerships - Tuba, Orsolya (2023)
The ambitious Sustainable Development Goals (SDGs) have sparked a multilateral interest in higher education (HE) development cooperation, including political, economic, and global responsibilities. However, there is a lack of critical evaluation of recent capacity development (CD) collaborations with partners from the Global South, particularly in the Finnish context. The study reveals how Finnish HE CD projects are guided by Sustainable Development Goal 4 (SDG4), as well as the successes and challenges that Finnish counterparts face when implementing these projects. The qualitative research methods used in the study were inspired by postcolonial theory and development studies. Despite the role of SDG4 in shaping Finnish global education development strategies, the main priorities of CD are based on Finnish expertise and are not always based on the needs of Global South partners, according to a thematic analysis of key policy and funding documents. Thematic analysis of semi-structured interviews with eight Finnish HE CD practitioners revealed struggles with funding instruments and project-based approaches, as well as a strong desire to improve partnerships so that they are more equal, ethical, and collaboratively developed. The experiences of Finnish counterparts and the underlying motives for establishing CD partnerships are discussed from a postcolonial perspective on the latent level to unpack the underlying global and national agenda driving North-South HE partnerships led by Finnish HEIs.